Cost-utility analysis of a preventive home visit program for older adults in Germany - Brettschneider, Christian; Luck, Tobias; Fleischer, Steffen; Roling, Gudrun; Beutner, Katrin; Luppa, Melanie; Behrens, Johann; Riedel-Heller, Steffi G; König, Hans-Helmut (BMC health services research, 2015)
Background Most older adults want to live independently in a familiar environment instead of moving to a nursing home. Preventive home visits based on multidimensional geriatric assessment can be one strategy to support this preference and might additionally reduce health care costs, due to the avoidance of costly nursing home admissions. The purpose of this study was to analyse the cost-effectiveness of preventive home visits from a societal perspective in Germany. Methods This study is part of a multi-centre, non-blinded, randomised controlled trial aiming at the reduction of nursing home admissions. Participants were older than 80 years and living at home. Up to three home visits were conducted to identify self-care deficits and risk factors, to present recommendations and to implement solutions. The control group received usual care. A cost-utility analysis using quality-adjusted life years (QALY) based on the EQ-5D was performed. Resource utilization was assessed by means of the interview version of a patient questionnaire. A cost-effectiveness acceptability curve controlled for prognostic variables was constructed and a sensitivity analysis to control for the influence of the mode of QALY calculation was performed. Results 278 individuals (intervention group: 133; control group: 145) were included in the analysis. During 18 months follow-up mean adjusted total cost (mean: +4,401 EUR; bootstrapped standard error: 3,019.61 EUR) and number of QALY (mean: 0.0061 QALY; bootstrapped standard error: 0.0388 QALY) were higher in the intervention group, but differences were not significant. For preventive home visits the probability of an incremental cost-effectiveness ratio <50,000 EUR per QALY was only 15%. The results were robust with respect to the mode of QALY calculation. Conclusions The evaluated preventive home visits programme is unlikely to be cost-effective. Trial registration Clinical Trials.gov Identifier: NCT00644826 .